Mycobacterial Characteristics and Treatment Outcomes in Mycobacterium abscessus Lung Disease. (10th November 2016) - Koh, Won-Jung; Jeong, Byeong-Ho; Kim, Su-Young; Jeon, Kyeongman; Park, Kyoung Un; Jhun, Byung Woo; Lee, Hyun; Park, Hye Yun; Kim, Dae Hun; Huh, Hee Jae; Ki, Chang-Seok; Lee, Nam Yong; et al.
Abstract : Several mycobacterial characteristics, including colony morphotype, susceptibility to macrolide antibiotics, and T28C substitution in the erm (41) gene, are helpful in predicting the treatment responses of patients with Mycobacterium abscessus lung disease. Treatment failures and recurrences are frequently caused by reinfection. Abstract: Background: Treatment outcomes of patients with Mycobacterium abscessus subspecies abscessus lung disease are poor, and the microbial characteristics associated with treatment outcomes have not been studied systematically. The purpose of this study was to identify associations between microbial characteristics and treatment outcomes in patients with M. abscessus lung disease. Methods: Sixty-seven consecutive patients with M. abscessus lung disease undergoing antibiotic treatment for ≥12 months between January 2002 and December 2012 were included. Morphotypic and genetic analyses were performed on isolates from 44 patients. Results: Final sputum conversion to culture negative occurred in 34 (51%) patients. Compared to isolates from 24 patients with persistently positive cultures, pretreatment isolates from 20 patients with final negative conversion were more likely to exhibit smooth colonies (9/20, 45% vs 2/24, 8%; P = .020), susceptibility to clarithromycin (7/20, 35% vs 1/24, 4%; P = .015), and be of the C28 sequevar with regard to the erm (41) gene (6/20, 30% vs 1/24, 4%; P = .035). Mycobacterium abscessus lung disease recurred in 5 (15%) patients after successful completion of antibiotic therapy. Genotypic analysis revealed that most episodes (22/24, 92%) of persistently positive cultures during antibiotic treatment and all cases of microbiologic recurrence after treatment completion were caused by different M. abscessus genotypes within a patient. Conclusions: Precise identification to the subspecies level and analysis of mycobacterial characteristics could help predict treatment outcomes in patients with M. abscessus lung disease. Treatment failures and recurrences are frequently associated with multiple genotypes, suggesting reinfection. Clinical Trials Registration: NCT00970801.